Molecular characterization of Trichogramma spp. in sugarcane (Saccharum officinarum) ecosystem in Punjab - KAUR, JASREET; JINDAL, VIKAS; SANGHA, KAMALDEEP SINGH (The Indian Journal of Agricultural Sciences, 2023)
Trichogramma chilonis (Ishii) is of great importance to biological control of many harmful lepidopteran pests of crops. There is a need to establish the species composition in the fields for differentiation among the species/strains in order to enhance efficiency of their practical application. This study aimed to catalogue the species of Trichogramma available in sugarcane in Punjab. The populations were collected from different districts of Punjab, viz. Gurdaspur, Shaheed Bhagat Singh Nagar, Patiala, Amritsar and Fazilka during 2017–18. The mtCOI gene of Trichogramma was amplified and sequenced for identification of species and assessing the genetic diversity. Nucleotide sequences of Trichogramma populations collected from different sugarcane growing districts of Punjab showed 99% homology with T. chilonis. Multiple alignments of mtCOI sequences showed three branches with Punjab populations similar to New Delhi, Bengaluru and Pakistan. This study confirms the successful establishment of T. chilonis in sugarcane ecosystem in Punjab.